Cognitive Behavior Therapy Improve Intolerance of Uncertainly in Type II Diabetes Mellitus Patients - Yulis Hati; Rosanti Muchsin; Rika Nurjannah Batubara (Universitas Prima Indonesia, 2025)
Diabetes mellitus (DM) is a chronic disease and silent killer characterized by hyperglycemia. Type 2 DM has become a global health crisis. This disease causes serious life-threatening health problems with high medical costs, decreased quality of life and increased mortality which causes uncertainty where patients feel they no longer care about their disease and the solution to overcome this with Cognitive Behavioral Therapy. Quantitative research type, Quasi-Experiment design with pretest-posttest. The population amounted to 319 people, sample selection by purposive means, a sample of 36 people. The instrument used a questionnaire. The statistical test used Wilcoxon Test. The results of the Wilcoxon test value = 0.000 < (0.005) means that there is an effect of cognitive bahavior therapy on intolerance of uncertainty in Type II Diabetes Mellitus patients at the Amplas Health Center in 2024. Based on the results of the study, it is concluded that there is an effect of cognitive bahavior therapy on intolerance of uncertainty in Type II DM patients. It is expected that DM patients with intolerance of uncertainly use non-pharmacological methods, namely cognitive behavior therapy to reduce intolerance of uncertainly.